Hadronic mass moments in inclusive semileptonic B meson decays. - Cronin-Hennessy, D; Lyon, A; Roberts, S; Thorndike, E; Coan, T; Fadeyev, V; Gao, Y; Maravin, Y; Narsky, I; Stroynowski, R; Ye, J; Wlodek, T; et al. (2001)
We have measured the first and second moments of the hadronic mass-squared distribution in B-->X(c)l nu, for P(lepton)>1.5 GeV/c. We find <m(2)(x)-m macro(2)(d)=""> = 0.251+/-0.066 GeV(2), <(M(2)(X)-<m(2)(x)>)(2)> = 0.576+/-0.170 GeV(4), where M macro(D) is the spin-averaged D meson mass. From that first moment and the first moment of the photon energy spectrum in b-->s gamma, we find the heavy quark effective theory parameter lambda(1) (in the modified minimal subtraction renormalization scheme, to order 1/M(3)(B) and beta(0)alpha(2)(s)) to be -0.24+/-0.11 GeV(2). Using these first moments and the B semileptonic width, and assuming parton-hadron duality, we obtain absolute value of V(cb) = 0.0404+/-0.0013.</m(2)(x)></m(2)(x)-m>